ECM remodeling-associated immune signatures and hub proteins: predictive markers and therapeutic targets for metastatic gastric cancer - Hu, Xinyue; Zhao, Kai; Shi, Yaoqiang; Liu, Zhongjian; Sun, Yi (Frontiers in Immunology, 2026)
BackgroundGastric cancer (GC) remains one of the most prevalent malignancies worldwide. A growing number of studies have identified the extracellular matrix (ECM) as a key regulator in gastric cancer development and metastasis. Gastric cancer cells interact with the ECM, modifying its composition and structure, thereby promoting tumor invasiveness and metastatic ability. However, the specific molecular mechanisms underlying these processes remain poorly understood.MethodsIn this study, we identified metastasis-related hub proteins in the extracellular matrix by proteomics, explored the differentiation trajectories of tumor cells at the single-cell levelidentified metastasis-related trajectories and metastasis-associated tumor cell subtypes, and experimentally verified the roles and mechanisms by which metastasis-associated ECM proteins regulate the migration and invasion of gastric cancer cells.ResultsOur proteomic analysis revealed 282 prognosis-related differential proteins between gastric cancer metastasis-free and metastasis-associated groups, including 77 extracellular matrix proteins. We constructed a protein-protein interaction (PPI) network and identified four core hub proteins using network centrality measures. Single-cell RNA sequencing provided a detailed landscape of gastric cancer cells, enabling exploration of the expression patterns of these hub proteins across different cell subtypes. Trajectory analysis uncovered distinct pathways associated with tumor metastasis and highlighted the regulatory roles of hub proteins in this process. We identified two key tumor cell subtypes critical for metastasis, and through cell communication analysis, identified significantly enriched pathways linked to metastatic progression. In vitro experiments further validated the functional role of Ribosomal Protein S29(RPS29) in the metastatic mechanisms of gastric cancer cells.ConclusionThis study not only reveals the complexity of ECM remodeling in the microenvironment of gastric cancer but also provides new perspectives and potential targets for future gastric cancer treatment and brings opportunities for the development of new therapeutics, which are expected to overcome the challenge of cancer metastasis.